`int x^3e^x dx` Find the indefinite integral

Expert Answers

An illustration of the letter 'A' in a speech bubbles

To evaluate the integral:` int x^3e^x dx` , we may apply "integration by parts": `int u *dv = uv- int vdu` .

Let: `u= x^3` then `du = 3x^2 dx`

     ` dv = e^x dx`  then `v = int e^x dx = e^x` .


Apply the formula for integration by parts, we get:

`int x^3e^x dx = x^3 e^x - int 3x^2e^xdx` .

                   `= x^3 e^x - 3 int x^2e^xdx.`

 To evaluate` int x^2 e^x dx` , we apply another set of integration by parts.

Let:    `u = x^2` then `du = 2x dx`

        `v=e^x dx` then `dv = e^x`

The integral becomes: 

`int x^2 e^x dx =x^2e^x - int 2xe^x dx`

Another set of integration by parts by letting:

`u = 2x` then `du =2dx`

`v=e^x dx` then `dv = e^x`

`int 2xe^x dx = 2xe^x - int 2e^x dx`

                    `= 2xe^x -2 e^x +C`

 Using `int 2xe^x dx =2xe^x - 2e^x +C` , we get:

`int x^2 e^x dx =x^2e^x - int 2xe^x dx`

                    `=x^2e^x - [2xe^x - 2e^x ]+C`

                    `=x^2e^x - 2xe^x + 2e^x +C`


 `int x^3e^x dx = x^3 e^x - 3 int x^2e^xdx` .

                      ` = x^3 e^x - 3 [x^2e^x - 2xe^x + 2e^x] +C`

                     `= x^3 e^x - 3x^2e^x +6xe^x -6 e^x +C`

Approved by eNotes Editorial Team